Molecular profiling of acute myeloid leukemia with Runx1-Runx1t1 fusion - Magdy Elbordiny; Reham AboElwafa; Abeer Elhadidi; Ashraf Elghandour; Salma Elmasry (Alexandria Journal of Medicine, 2024)
Introduction Acute myeloid leukemia (AML) is a heterogeneous hematologic malignancy characterized by the clonal expansion of immature myeloid cells. Among the genetic alterations in AML, the RUNX1- RUNX1T1 fusion, resulting from the t (8; 21) (q22; q22.1) translocation, is common and linked with a favorable prognosis. However, the complete mutational profile contributing to leukemogenesis remains unclear. This study characterizes the mutational profile of the RUNX1-RUNX1T1 fusion in AML using Next-Generation Sequencing (NGS).Methods Twenty-four newly diagnosed AML patients were selected. DNA and RNA were extracted from bone marrow aspirate samples, and libraries were prepared using the Ion AmpliSeq™ Library Kit. Sequencing was performed on the Ion S5™ system, and data were analyzed using Torrent Suite™ and Ion Reporter™ Software. Variants were annotated, and their clinical significance was assessed via ClinVar. In silico prediction tools, including SIFT and PolyPhen-2, were used for functional impact assessment.Results Patients with RUNX1-RUNX1T1 fusion (n = 3) demonstrated higher initial peripheral blood and bone marrow blast counts and a pronounced prevalence of CD56 and CD19 positivity. The average number of mutations in KIT and NF1 was higher in the fusion group (p = 0.021 and p = 0.049, respectively). In total, 228 genetic variants were identified, with most associated with transcription/kinase signaling pathways (36.8%). Epigenetic regulators were the next most common category (21.5%). ClinVar data revealed pathogenic variants predominantly in the KIT gene, including two missense mutations, p.Asp816Val and p.Asp816Ala, at exon 17. Unique variants were identified exclusively in RUNX1-RUNX1T1 patients, including eight non-reported variants. Among these, a TET2 variant (p.Pro1367Leu) was predicted to have deleterious effects based on in silico tools.Conclusion The molecular profiling of RUNX1-RUNX1T1 fusion offers crucial insights into AML’s genetic landscape. Identifying therapeutic targets and novel variants broadens our understanding of mutations, presenting new research opportunities and potential interventions.